Troponin T correlates with MRI results in neonatal encephalopathy. (13th April 2020) - Sweetman, Deirdre U.; Kelly, Lynne; Hurley, Tim; Onwuneme, Chike; Watson, R. William Gordon; Murphy, John F. A.; Slevin, Marie; Donoghue, Veronica; Molloy, Eleanor J.
Abstract: Aim: Troponin is a sensitive marker of asphyxia in term infants mirroring the myocardial injury sustained in global hypoxia‐ischaemia. In addition, troponin is a sensitive marker of severity of stroke in adults and neonatal encephalopathy (NE). We aimed to examine the relationship between troponin T in infants with perinatal asphyxia and brain injury on MRI and correlate with neurodevelopmental outcome. Methods: Serum troponin was sampled in infants requiring resuscitation at birth and/or neonatal encephalopathy in a tertiary referral neonatal centre. Birth history, clinical parameters, neuroimaging and developmental outcome (Bayley Scores of Infant Development [BSID] III) were evaluated. Results: Infants with perinatal asphyxia (n = 54) had serum troponin T measured and 27 required therapeutic hypothermia. Troponin T levels on days 1 and 2 were predictive of need for TH, development of seizures and grade II/III NE (AUC = 0.7; P ‐values < .001), troponin T levels on days 1, 2 and 3 were highly significant predictors of mortality (AUC = 0.99, P ‐values .005). The cut‐off values of troponin T for best prediction of mortality were 0.84, 0.63 and 0.58 ng/mL on days 1, 2 and 3, respectively. Troponin T on day 3 of life was predictive of injury in the combined area of basal ganglia/watershed on MRI (AUC 0.70; P ‐value = .045). Conclusion: Infants with brain injury on neuroimaging following perinatal asphyxia had significantly elevated serum troponin, and troponin also correlated with developmental scores at 2 years. Further studies combining troponin and MRI may assist in the classification of neonatal brain injury to define aetiology, prognosis and response to treatment.